Molecular epidemiology and pathogenomics of extended-spectrum beta-lactamase producing- Escherichia coli and - Klebsiella pneumoniae isolates from bulk tank milk in Tennessee, USA - Gelalcha, Benti D.; Mohammed, Ruwaa I.; Gelgie, Aga E.; Kerro Dego, Oudessa (Frontiers in Microbiology, 2023)
The rise in ESBL-producing Enterobacteriaceae in dairy cattle farms may pose a risk to human health as they can spread to humans through the food chain, including raw milk. This study aimed to determine the status and pathogenic potential of extended-spectrum beta-lactamases (ESBL) producing-E. coli and -Klebsiella spp. isolates from bulk tank milk (BTM). Thirty-three BTM samples were collected from 17 dairy farms and screened for ESBL-E. coli and -Klebsiella spp. on CHROMagar ESBL plates. CHROMagar ESBL plate allows color-based differentiation in which ESBL-E. coli is dark pink or reddish whereas ESBL-Klebsiella spp. is metallic blue. All isolates were confirmed by MALDI-TOF MS and subjected to antimicrobial susceptibility testing and whole genome sequencing. Ten presumptive ESBL-producing bacteria, eight E. coli, and two K. pneumoniae were isolated. The prevalence of ESBL-E. coli and -K. pneumoniae in BTM was 21.2% and 6.1%, respectively. ESBL-E. coli were detected in 41.2% of the study farms. Seven of the ESBL-E. coli isolates were MDR. The two ESBL-producing K. pneumoniae isolates were resistant to ceftriaxone. Seven ESBL-E. coli strains carry the blaCTX-M gene, and five of them co-harbored blaTEM-1. ESBL-E. coli co-harbored blaCTX-M with other resistance genes, including qnrB19, tet (A), aadA1,), floR, sul2, and chromosomal mutations (gyrA, gyrB, parC, pare, and pmrB). Most E. coli resistance genes were associated with mobile genetic elements, mainly plasmids. Six sequence types (STs) of E. coli were detected. All ESBL-E. coli were predicted to be a human pathogen. Four STs (three ST10 and ST69) were high-risk clones of E. coli. Up to 40 virulence markers were detected in all E. coli isolates. One of the K. pneumoniae was ST867; the other was novel. K. pneumonia isolates carried three types of beta-lactamase genes (blaCTX-M, blaTEM-1 and blaSHV). The novel ST also carried a novel IncFII(K) ST. Detection of high-risk clones of MDR ESBL-E. coli and ESBL-K. pneumoniae in BTM indicates that raw milk could be a reservoir of potentially zoonotic ESBL-E. coli and -K. pneumoniae.